Tanggung Jawab Penjual Atas Cacat Tersembunyi dalam Jual Beli Menurut Hukum Positif Indonesia - Nadia Putri Ibtisamah; Arief Suryono (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Hidden defects are defects in goods that cannot be directly known by the buyer at the time of the transaction. In the Civil Code, hidden defects are regulated in Article 1491 of the Civil Code and Article 7, paragraph (2) of Law No. 8 of 1999 concerning Consumer Protection. This study aims to analyze the seller’s liability for goods containing hidden defects using a normative approach. The findings indicate that the seller's liability for hidden defects is strict (strict liability), obligating the seller to provide compensation to the buyer who suffers a loss. A harmed consumer is entitled to claim compensation in the form of returns, replacements, or reimbursements. Legal protection is essential to create a balance of rights and obligations within the legal relationship between consumers and business actors. Enforcing seller liability also promotes compliance with quality standards and increases consumer awareness of their rights. Therefore, the existing regulations play a significant role in ensuring justice and guaranteeing consumer safety in sales transactions.